Instructivo operacional para puesta en marcha y parada de servicio bomba de transferencia de crudo de la estación J-25. (2020)
The following degree project was developed in order to provide accurate, systematic, shallow, methodical and comprehensive information that contains all the instructions, step by step, responsibilities and information of each of the processes carried out in pumping, with the purpose of ensure all activities of the operation. Each of the sections to this instruction was carried out in a standardized way where it allows to unify procedures in the development of their daily activities and that these activities comply with the quality parameters according to current legal and technical regulations, allowing each activity to be carried out. reliable, safe and timely manner. Where description and updating of the operating procedures of the equipment used for handling crude oil is carried out in order to standardize these procedures.